2020
DOI: 10.3389/fpls.2020.554520
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DREBA4-Type Transcription Factor (SlDREBA4), Which Contributes to Heat Tolerance in Tomatoes

Abstract: Dehydration-responsive element binding (DREB) transcription factors play crucial regulatory roles in abiotic stress. The only DREB transcription factor in tomato (Solanum lycopersicum), SlDREBA4 (Accession No. MN197531), which was determined to be a DREBA4 subfamily member, was isolated from cv. Microtom using high-temperature-induced digital gene expression (DGE) profiling technology. The constitutive expression of SlDREBA4 was detected in different tissues of Microtom plants. In addition to responding to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In tomato, overexpression of DREB‐ TINY1 suppresses GA20ox1 and GA20ox2 expression, reduces GA levels, inhibits growth, and promotes tolerance to drought (Li et al ., 2012). The tomato TINY1 was also induced by high temperatures and its downregulation resulted in susceptibility to heat stress (Mao et al ., 2020). Our results showed that the loss of TINY1 had no effect on the suppression of GA20ox1 and GA20ox2 by drought, suggesting that TINY1 is not the drought‐induced regulator of these GA20oxs .…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, overexpression of DREB‐ TINY1 suppresses GA20ox1 and GA20ox2 expression, reduces GA levels, inhibits growth, and promotes tolerance to drought (Li et al ., 2012). The tomato TINY1 was also induced by high temperatures and its downregulation resulted in susceptibility to heat stress (Mao et al ., 2020). Our results showed that the loss of TINY1 had no effect on the suppression of GA20ox1 and GA20ox2 by drought, suggesting that TINY1 is not the drought‐induced regulator of these GA20oxs .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CBF2 and CBF3 of Arabidopsis, bind to the DRE, being also related to low-temperatures (Wu et al, 2017;Kidokoro et al, 2020). Mao et al (2020) confirmed that SlDREBA4 specifically bound to the DRE elements of the downstream Hsp genes and contributed to heat tolerance in tomatoes (Solanum lycopersicum). However, recent study indicated that some DREB was also involved in certain processes during the plant life cycle via binding to DRE/CRT motifs.…”
Section: Figurementioning
confidence: 91%
“…The APETALA2/ethylene response factor (AP2/ERF) transcription factor (TF) is a superfamily of plant species that plays multiple roles in plant growth and development, stress tolerance, and the integration of phytohormonal signals [ 3 ]. Since the first AP2/ERF TF AP2 was identified in Arabidopsis as a controller in flower and seed development, several genes of the DREB and ERF subfamily have been explored for their molecular roles and mechanisms, particularly in biotic and abiotic stresses [ 9 , 11 , 14 , 37 39 ]. Previous studies on the function of AP2/ERF have mainly focused on model plants and crops, and some studies have explored the AP2/ERF genes of trees, mainly from Populus and Broussonetia papyrifera [ 40 43 ].…”
Section: Discussionmentioning
confidence: 99%